The President's Photographer: Fifty Years Inside the Oval Office - John Bredar (National Geographic, 2010)
This behind-the-scenes look at the lives of our recent Commanders in Chief features the images and recollections of the nine professionals who have served as official White House photographers, including Pete Souza, the Chief Official White House Photographer for President Obama and previously an Official White House Photographer for President Reagan. The President's Photographer is the intimate story of the men and women who are both visual historians and key links between the public and the Presidents.